Abstract or concrete? The impact of regional typicality and advertising appeal types on consumption intention toward geographical indication products - Wang, Dan; Xu, Yueyan; Li, Wanjun; Li, Yanjun (Frontiers in Psychology, 2024)
The essential characteristic of geographical indication products is the association of the products with their region of origin. However, consumers have different associations between products and their region of origin (i.e., different regional typicality) according to different geographical indication products. In this regard, this research aims to explore how to adopt supporting advertising appeal types to improve consumers' attitudes and intentions toward geographical indication products with different regional typicality. To this end, this article proposes and tests the interaction between regional typicality and advertising appeal types on consumption intention toward products and the underlying mechanism and boundary conditions of this effect. Using three studies, this research finds that the adoption of abstract (vs. concrete) appeal is more likely to enhance consumption intention toward products when the geographical indication products have high regional typicality. Moreover, the reverse is true when the geographical indication products have low regional typicality. Furthermore, the results show that processing fluency mediates the interaction effect. In addition, the high (low) regional typicality and abstract (concrete) appeal on consumption intention toward products are more significant in the distant (close) spatial distance condition. In this way, this research provides a new perspective for studying consumer behavior with respect to geographical indication products and has implications for promoting the sales of geographical indication products and enhancing the brand value of geographical indication.